RUNTUHNYA WATAK POLIMORPIK KIAI DALAM KULTUR MASYARAKAT MADURA - Suhermanto (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
Relation between a kiai, and his people as visualized on Madura culture, became a reality that deserve further reviewed by particularly concerning the tides especially about change the configuration relation patron-clien factors. Indeed, when viewed in passing; relation that is a derivative and obedience residents madura kiai that tends towards (fanatics-doctrine) having very small opportunities for change. However, after reformation era, piecemeal society also starting to separated, be two camps that face each other. They are support one kiai to opposed kiai which incidentally is having problems with kiai being patron of them. Changing the pattern of relationships kiai and people in the tribe of madura in the era of reform, at least will also have important implications, although the implications of the most real this time only on political dimensions. Relationships between kiai and the community in madurese, can be said as patron-client relationships, having characteristics that clients will honor and obey the patron without reserve. In addition, model of leadership that looked at relationships between kiai and the community in madura often known by term pholimorphic, is a leader who has an important influence in some field at once. This fact automatically make people madura impressed favoring one kiai and opposed other kiai, who is from madurese cultural ambivalence prevailing earlier.